SLEEP DISORDERS AND THE RISK OF MYOCARDIAL INFARCTION AND STROKE IN MEN OF NOVOSIBIRSK CITY - V. V. Gafarov; E. A. Gromova; I. V. Gagulin; A. V. Gafarova; D. O. Panov (Российский кардиологический журнал, 2014)
Aim. To estimate the risk of myocardial infarction (MI) and stroke in economically- active men (25-64 y.o.) with sleep disorders during 14-years period. Material and methods. In the 3rd screening for WHO program "MONICA- psychosocial" the random relevant selection was studied of the men 25-64 y.o. in Novosibirsk in the year 1994 (n=657, mean age 44,3±0,4, response — 82,1%). The program of screeing examination included the registration of social and demographic data, sleep disorders assessment with Jenkins C. D. score. During 14-year perion 30 MIs and 22 strokes registered. Statistical analysis was done with SPSS v. 11.5 software. We used Pirson %2 criteria, and for Hazard Ratio (HR) — Cox-regression. Reliability in all types of analysis was with the cut-off p<0,05. Results. The prevalence of sleep disorders in men 25-64 y.o. was 48,3%; "satisfactory" self sleep assessment was in 39,6%; "bad" — 7,6%; "very bad" — 1,1%. As "good" their sleep marked 46,2% and as "very good" — 5,6%. In men with the MI developed "good" sleep mark was 36,8%, "satisfactory" — 44,7%, "bad" — 18,4% (x2=2,402, v=4, р>0,05). In those developed stroke in 47,1% the mark was "good", in 23,5% — "satisfactory", and 29,4% marked bad sleep (x2=6,234, u=2, р<0,05).In Cox Regression the MI 5-year risk in persons of 25-64 y.o. with sleep disorders was HR=2,4, during 10 years — HR=2,6, and during 14 years HR=2,3; for stroke, respectively, 3,9; 2,72; 1,5.A serious influence on the MI and stroke risk among men having sleep disorders, made family status. MI and stroke risk is much higher in single, divorced or widowed. The highest risk of MI and stroke had men with sleep disorders having low education level and on strenuous physical labour.Conclusion. Sleep disorders is important an influencing psychosocial risk factor for MI and stroke.